The Influence of Price, Promotion, and User Experience on the Decisions of Users of Grab Online Motorcycle Taxi Transportation Services in Makassar City - Hasbiah, Sitti (International Humanity Advance, Business & Sciences, 2025)
This study aims to determine the influence of Price, Promotion, and User Experience simultaneously and partially on the Decision to Use Grab Online Motorcycle Taxi Transportation Services in Makassar City. This study used 100 samples, the sampling technique used nonprobability sampling with Purposive sampling. The type of research used is associative, the data collection technique used is a questionnaire. The analysis technique used is Multiple Linear Regression analysis, F Test, T Test, and Determination Coefficient with a significance level of 10%. The results of the study show that. (1) There is an influence of Price, Promotion, and User Experience simultaneously/together on the Decision to Use Grab Online Motorcycle Taxi Transportation Services in Makassar City with an F count of 28,990> F table 2.14 with a significance level of 0.000 <0.1. (2) There is a partial influence of Price on the Decision to Use Grab Online Motorcycle Taxi Transportation Services in Makassar City with a t count of 2,659> t table 1,660. (3) There is a partial influence of Promotion on the Decision to Use Grab Online Motorcycle Taxi Transportation Services in Makassar City with a t-count value of 2.078 > t-table 1.660. (4) There is a partial influence of User Experience on the Decision to Use Grab Online Motorcycle Taxi Transportation Services in Makassar City with a t-count value of 2.036 > t-table 1.660.